The rise of individual personhood in early medieval China - Sernelj, Tea (Asian studies, 2024)
The term “Early Medieval China” usually refers to the Wei Jin period, also known as the Wei Jin Southern and Northern dynasties (Wei Jin Nanbei chao?????). This era was characterized by extreme sociopolitical circumstances, marked by constant instabil-ity, upheavals, wars, corruption, intrigues, external invasions and the exhaustion of the population. These conditions led to significant and unprecedented social and intellectual transformations that profoundly impacted Chinese culture, especially in the fields of phi-losophy and art. This article explores the cultural and philosophical ideas of the period that contributed to the rise of individual personhood, which emerged as a response to the suppressive and authoritarian Han Confucianism, which was heavily influenced by Le-galist doctrines. Neo-Daoism, the most important stream of thought that arose from the political turmoil of the period, provided intellectuals with a refuge during these traumatic times, allowing them to explore new ways of philosophizing and experiencing an aesthetic way of living. The article examines the philosophical inquiries of the School of Profound Learning (Xuanxue??) and Pure Conversations (Qingtan??) movement, which gave rise to self-awareness and fostered new perspectives on individual personhood.
Keywords: individual personhood; individualna osebnost; Neo-Daoism; neodaoizem; obdobje Wei Jin; Profound Learning (Xuanxue??) and Pure Conversations (Qingtan??); sedem modrecev iz bambusovega gaja; Seven Sages of the Bamboo Grove; šola misterijev (Xuanxue??) in čisti pogovori (Qingtan??); Wei Jin Period